2020
DOI: 10.21203/rs.3.rs-37809/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ergogenic effect of pre-exercise chicken broth ingestion on a high-intensity cycling time-trial

Abstract: Background Chicken meat extract is a popular functional food in Asia. It is rich in the bioactive compounds carnosine and anserine, two histidine-containing dipeptides (HCD). Studies suggest that acute pre-exercise ingestion of chicken extracts has important applications towards exercise performance and fatigue control, but the evidence is equivocal. This study aimed to evaluate the ergogenic potential of the pre-exercise ingestion of a homemade chicken broth (CB) vs a placebo soup on a short-lasting, high-int… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Despite the observed improvements in performance in several studies [ 13 , 15 , 16 ], no differences were found in plasma lactate concentration, pH, bicarbonate concentration, and glutathione as oxidative stress marker. This indicates that the benefits currently can not be attributed to the buffering or antioxidant effect of HCD, which are usually described as their main functions [ 17 ].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite the observed improvements in performance in several studies [ 13 , 15 , 16 ], no differences were found in plasma lactate concentration, pH, bicarbonate concentration, and glutathione as oxidative stress marker. This indicates that the benefits currently can not be attributed to the buffering or antioxidant effect of HCD, which are usually described as their main functions [ 17 ].…”
Section: Introductionmentioning
confidence: 74%
“…The currently used ratio of 1:1 CAR:ANS seems to be a valid ergogenic approach. The more natural ratio of CAR to ANS in chicken meat, 1:2 to 1:3 (depending on meat source) may also work for acute pre-exercise supplementation [ 15 , 16 ]. Finally, whether pure ANS is effective, remains to be established.…”
Section: Discussionmentioning
confidence: 99%